The phases of culture shock engaged by the main character Sashi as reflected in English Vinglish film - Thalitha Natasya Fitri; Afina Murtiningrum (EduLite: Journal of English Education, Literature and Culture, 2020)
This study explores the culture shock portrayed in Sashi’s character of English Vinglish film by Gauri Shinde. The purpose of this study is to describe the kinds of phases of culture shock engaged by Sashi as the analyzed character. This study used descriptive qualitative method. The English Vinglish film by Gauri Shinde and the film script were the primary data of the study, whereas, the secondary data were taken from the books, journals, and articles that related to the research. The results of the study shows that Sashi as the main character in English Vinglish film encounters four phases of culture shock; they are honeymoon, crisis, recovery, and adjustment.